An in situ experimental method for monitoring the viscosity change and oil amount during the sliding test - Shiomi, Hiroshi; Obara, Shingo (Frontiers in Mechanical Engineering, 2025)
This study measures the changes in the viscosity and oil volume of lubricants in a vacuum sliding test under starved EHL to evaluate the lubrication life of a small amount of lubricants, and investigates their time transition and a mechanism of lubrication life. Starved EHL is observed in ball bearings lubricated with a small amount of lubricant, which require low friction torque even at high speeds, such as bearings used in artificial satellites. Under starved oil conditions, the oil film formed in the contact area becomes thin, so it is important to accurately estimate the oil film thickness in order to avoid solid contact. Since viscosity and oil volume affect the oil film thickness in the contact area, it is important to know how they change during the test. In this study, a method was proposed to measure viscosity and oil quantity without breaking the vacuum during a sliding test using a small amount of oil in a vacuum. Using this method, changes in viscosity and oil quantity until the end of lubrication life were measured in a sliding test using a small amount of MAC. As a result, an increase in viscosity and a decrease in oil quantity were observed. The measured results discussed the relationship between the increase in viscosity and the frictional work or sliding distance and indicated that the lubrication condition at the end of lubrication life was severely starved.